KARAKTERISTIK PENDERITA BATU SALURAN KEMIH YANG DIRAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2015-2016 - Sinta M Y S; Rasmaliah .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Urolithiasis disease is the third mosted common cause of pain in the urinary tract after Urinary Tract Infections (UTI) and Benign Prostatic Hiperflasia (BPH). In the United States, about 13% of men and 7% of women will establish kidney stone during their lifetime and prevalence continues to increase in industrialized countries. Urolithiasis can attack people around the world, without exception for resident of Indonesia. The aims to identify characteristics of  Urolithiasis who hospitalized at Santa Elisabeth Hospital Medan in 2015-2016 . This is a descriptive study with case series design. Population is all data of patient’s Urolithiasis who was hospitalized in Santa Elisabeth General Hospital Medan 2015-2016 are 332 patient data, 181 samples taken by simple random sampling. The results shows that the largest proportion of Urolithiasis patients was ≥45 years old (57,7%), male (63,5%), Bataknese (86,7%), ProtestantChristian (57,5%), Entrepreneur ( 27.6), married (89.5%),and Outside of Medan (57.5%), upper urinary tract (97.8%),> 1 complaint (55,8%), hydronephrosis ( 42.5%), normal creatinin (47,5%), normal ureum (65,2%), operation treatment (50.8%), average lenght of stay at hospital is 5 days, healed (67,4%) There was no significant difference in proportion between genre based on the location of stone, the main complaint based on the location of stone, medical treatment based on the location of stone, medical treatment based on the creatinine of blood, medical treatment based on ureum of blood, the average lenght of stay at hospital based on the location of the stone average lenght of stay at hospital. There was a significant difference in proportion between in the average length of based on the medical management. It was rekomended that patient that patients who have symptomps of Urolithiasis to get medical treatment immediately.   Key Words: Urolithiasis, Patient Characteristics, Santa Elisabeth Hospital